The Impact Of Dual Reporting Structure On Employees: A Study Among Functional Managers In Telekom Malaysia - Mohamed Zamzam, Kairul Annuar (2000)
This study is important to gain insight of the employees perspective on dual reporting structure to enable the company to implement recommendations made in this study for its survival and for its long-term success. With the potential conflicts, the change in job characteristics, the higher level and the process of interaction within the group, this study examines the impact of dual reporting structure to job satisfaction and the level of stress. This paper provides empirical evidence relating this impact.